2014
DOI: 10.2224/sbp.2014.42.9.1409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Content Characteristic of Short Message Service Advertising on Consumer Attitudes

Abstract: We examined the influence of the overall content characteristic of short message service (SMS) advertising on consumer attitudes toward advertising on mobile devices. Attitudes of 246 Chinese (145 women, 101 men) toward permission-based SMS advertising received on electronic products were measured using structural equation modeling. Results showed that of the 4 dimensions of the overall content characteristic, entertainment, informativeness, and credibility positively and significantly influenced the attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
2
13
0
1
Order By: Relevance
“…If consumers highly rate advertising value then they are more likely to have favorable attitudes towards the advertisements and vice versa. This result tallies with extant literature on consumer's attitudes to advertising such as Tsang, Ho, and Liang (2004); Petrovici and Marinov (2007) and Lin, Zhou and Chen (2014) amongst others.…”
Section: H4supporting
confidence: 85%
“…If consumers highly rate advertising value then they are more likely to have favorable attitudes towards the advertisements and vice versa. This result tallies with extant literature on consumer's attitudes to advertising such as Tsang, Ho, and Liang (2004); Petrovici and Marinov (2007) and Lin, Zhou and Chen (2014) amongst others.…”
Section: H4supporting
confidence: 85%
“…Zhang and Mao ( 2008 ) held that perceived informativeness and perceived entertainment were components of perceived utility, and Rohm et al ( 2012 ) explored the issue of whether perceived utility was a determinant of attitude toward mobile marketing. Furthermore, recent research showed that advertisements with more information than usual and a high level of entertainment can be readily accepted (Lin et al, 2014 , 2016 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Content marketing implies the creation of content whose primary goal is to make an impression, produce a relevant value and place an idea of a product or service in that manner for a particular target group. In the literature, content relevance is treated as the usefulness of information for the consumer [20]. In order to ensure brand management in a virtual space, there is a constant need for offering new, relevant content and maintaining regular contact with the buyer [21].…”
Section: Literature Reviewmentioning
confidence: 99%